The institutionalization of Syriza party in greece. - Balla, Evanthia (2018)
Since the 2008 financial crisis, the European Union has been confronted with an important existential crisis. This crisis has led to major financial bailouts in various Member States, forcing them to give up large portions of their financial sovereignty to the EU. The EU’s harsh doctrine of endless spending cuts caused a severe economic and social turmoil and a surge in anti-EU sentiment throughout Europe. In addition, many new parties arose in the European political scene in recent years, such as the Five Star Movement in Italy, the Ciudadanos and Podemos in Spain, the Alternative for Germany, the Greek parties of Syriza, Golden Dawn, To Potami, ANEL as well as La République en Marche in France. These parties differ significantly regarding their ideology, their creation and their financing. The rise of some of these parties is related to an intensification of populism and extremism all around Europe. Under this prism, the present article focuses on Greece’s characteristic example of Syriza’s birth and rise. In order to evaluate the institutionalization of Syriza and draw some specific conclusions over its political impact, one needs to respond to the following questions: What is the political, social and economic background inside which this party was formed? What is the relation between the old Greek political system and Syriza’s birth? What are Syriza’s composition and electorate?